Узагальнене відокремлення змінних і точні розв'язки нелінійних рівнянь - Баранник, Т.А.; Баранник, А.Ф.; Юрик, І.І. (Український математичний журнал, 2010)
Рассматривается обобщенная процедура разделения переменных нелинейных уравнений гиперболического типа и уравнений типа Кортевега - де Фриза. Построен широкий класс точных решений этих уравнений, которые нельзя получить методом С. Ли и методом условных симметрий. We consider a generalized procedure of separation of variables in nonlinear hyperbolic-type equations and Korteweg–de-Vries-type equations. We construct a broad class of exact solutions of these equations that cannot be obtained by the Lie method and method of conditional symmetries.